Transforming teams : tips for improving collaboration and building trust - St. John, Claudia (CRC Press, 2016)
Human resources and management consultants are frequently asked to help their clients address fundamental breakdowns within their organizations. More often than not, these breakdowns occur between conflicting functional areas, such as sales and customer service, sales and operations, or creative and operations management. This book explains why these breakdowns occur and details what you can do to correct them.A motivational management tale, Transforming Teams: Tips for Improving Collaboration and Building Trust is based on the author's real-world experience as a consultant helping companies resolve breakdowns in collaboration and trust at the workplace. Using a narrative style to illustrate problem-solving in action, the book follows the challenges faced by a company CEO and her team as they address three central precepts: that all relationships are reparable, that the use of direct language is fundamental, and that members of a team can fix only one thing, themselves.As the story unfolds, readers follow along and learn the three communication minefields that can derail and disrupt effective teamwork: breaking promises, avoiding conflict, and not holding each other accountable. Readers gain important insights as the characters end up improving their collaboration by recognizing the interrelated components of trust and understanding their own behavioral style and the styles of others.Although there's no silver bullet for solving team conflict, there are a number of proven tools and strategies that can help teams improve collaboration and productivity. This book presents these tools in a manner that any front-line manager can immediately deploy to help team members identify challenges objectively and take responsibility for improving the team dynamic.